2020
DOI: 10.3390/nu12092816
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Methods to Determine Added Sugars Intake to Assess the Association of Added Sugars Intake and Micronutrient Adequacy

Abstract: Different methods for determining the effect of added sugars intake among children and adults on meeting recommended nutrient intakes were compared using 24 h dietary recall data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014. Four methods were used to determine deciles of added sugars intake (as the percentage of total calories): 1 day intake, 2 day average intake, and individual usual intake (UI) determined with the National Cancer Institute (NCI) and the multivariate Markov Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The average study population mean/median age was 25 years old (mean/median range: 2.08 to 52.56 years), with 15 studies on child/adolescent populations below a mean/median age of 18 years. One study did not report the mean or median age [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average study population mean/median age was 25 years old (mean/median range: 2.08 to 52.56 years), with 15 studies on child/adolescent populations below a mean/median age of 18 years. One study did not report the mean or median age [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies from 15 articles reported on associations between dietary intakes of sugar and fiber [ 13 , 14 , 16 , 17 , 19 , 22 , 24 , 25 , 26 , 27 , 30 , 31 , 33 , 36 , 38 ], and the results are presented in Supplemental Table S4 along with factors accounted for by each study’s design or analysis. Most of these studies (62.5%) were rated as moderate for potential bias (neutral ROB) due to the study design, but other studies that only had one dietary intake measure and that did not control for important confounders were rated as high for potential bias (poor ROB; see Supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on all foods and drinks ingested, including their corresponding USDA Food and Nutrient Database for Dietary Studies (FNDDS) code, time and place of eating, quantity (g), and calories, were obtained from the two 24 h dietary recalls in each NHANES cycle (the first carried out in person and the second over the phone 3 to 10 days later) [17]. Three indicators of added sugars intake were created from each recall day, which were then averaged across the two days [18]. One indicator reflected the amount of added sugars intake (g/day).…”
Section: Methodsmentioning
confidence: 99%